KEJAHATAN PERANG (WAR CRIMES) DALAM BERBAGAI INSTRUMEN HUKUM INTERNASIONAL - Aji Wibowo (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2005)
War Crimes dalam London Agreement on War Criminals 1945 (Agreement for the Prosecution and Punishment of the Major War Criminals of the European Axis) Dal am London Charter, war crimes hanyalah salah satu yurisdiksi dari Nuremberg Trial yang terdapat dalam Pasal 6 (b) Piagam, yaitu sebagai berikut: "War Crime: namely, violations of the laws or customs of war. Such violations shall include, but not be limited to, murder, ill treatment or deportation or deportation to slave labour or for any other purpose of civilian population of or in occupied territory. Murder or ill treatment of prisoner of war or person on the seas, killing of hostages, plunder of public or private property, wanton destruction of cities, towns or villages, or devastation not justified by military necessity."1